Meningkatkan Pemahaman Anak-anak Mengenai Perkalian dan Pembagian dalam Pelajaran Matematika - Marthin Juanto P. Nainggolan; Malida Putri (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Mathematics is one of the fields of study taught in schools. Both elementary schools, junior high schools and public high schools. In Mathematics Lesson there are various kinds of material presented, starting from Multiplication, Addition, Division, Subtraction, Trigonometry, and much more. Learning Mathematics at school is expected that all students can know numbers and be able to count, because in the real world and work in mathematics it is very important so that there are no such things as Number Illiteracy and Calculation Stuttering. But who would have thought that there were many children who still did not understand mathematics, one of them was the children at the Panti Asuhan Solaya (PASO), the children complained that they did not understand Mathematics material, namely Multiplication and Division. the interesting subject of Mathematics and the difficulty of Mathematics. In this complaint, children need motivation to be enthusiastic and learn mathematics while playing so that children do not get bored in learning. And to overcome these problems optimally, Mini Project Practicum 2 was carried out, where the project used the Group Work Intervention method which consisted of several stages, namely Assessment, Planning, Intervention, Monitoring, Evaluation, and Termination. The implementation of the intervention method is expected to have a good impact on children.